(untitled) (Journal of Bangladesh Academy of Sciences, 2025)
A field experiment was accomplished at the Horticulture Farm, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh, from October to December 2021. The single-factor experiment was laid out in a randomized complete block design (RCBD) with three replications to evaluate the influence of Clybio as a bio-stimulant on the growth and yield performance of ornamental sunflower. The "Hybrid Ornamental Sunflower (F1)" (Vincent Choice) variety was utilized. The experiment consisted of three treatments, viz., C1: No Clybio application (Control), C2: Clybio @ 4 ml/L, and C3: Clybio @ 6 ml/L, which were applied in a foliar manner to the leaves and surrounding soil, respectively. Each treatment exhibited notable variations based on data on various vegetative growth, flower yields, and quality standards. The study revealed that plants treated with C3 (Clybio @ 6 ml/L) showed superior vegetative growth and yield-attributing performance, including the tallest plant height (110.0 cm), the maximum number of leaves per plant (33.2), highest SPAD value (34.4), maximum leaf area (140.6 cm2), maximum flower head size (14.3 cm), maximum ray floret area (6.0 cm2), maximum ray floret numbers per flower (31.8), long flower vase-life (8 days), and maximum number of secondary flowers (kid’s flower) per plant (12.2). On the contrary, the shortest plant height (99.9 cm), the minimum number of leaves per plant (30.2), lowest SPAD value (32.0), minimum leaf area (127.4 cm2), minimum flower head size (12.0 cm), minimum ray floret area (4.6 cm2), minimum ray floret numbers per flower (29.9), short flower vase-life (5 days), and minimum number of secondary flowers (kid’s flower) per plant (10.0) were observed in C1 (Control) treatment. The most amazing aspect was that this ornamental sunflower also produced numerous commercially valuable secondary flowers (kid’s flowers), which provided additional income to the producers. So, considering the aforementioned findings, the C3 (Clybio @ 6 ml/L) treatment proved the best promising prospect for producing high-quality ornamental sunflowers. J. Bangladesh Acad. Sci. 49(1); 21-29: June 2025